Potential Review Assessment with 9 Box Model for Talent Management of State-Owned Company Employee - Rifda Alda Ufaira; Rosatyani Puspita Adiati (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The individual potential review assessment is carried out on the basis of a comprehensive evaluation that aims to provide an in-depth picture of the current performance and future potential of an individual employee with the position of Industrial Relations Staff at State-Owned Company X. In addition, through this process, the organization can identify strengths, development areas, and the readiness of employees to take on more strategic roles. Data collection was carried out through several methods, namely psychological measurement, using standardized psychometric test tools to assess cognitive, personality, and behavioural competencies; interviews, to explore employees' motivations, career aspirations, and readiness for new challenges; as well as performance assessment data, as objective comparison material from the results of the evaluation of direct superiors. Based on the results of the analysis, the subjects showed performance that was included in the